The Little house cookbook - Walker, Barbara M. (New York : Harper & Row, 1979)
Recipes based on the pioneer food written about in the "Little House" books of Laura Ingalls Wilder, along with quotes from the books and descriptions of the food and cooking of pioneer times.
Includes bibliographical references and index.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile literature; Wilder, Laura Ingalls, -- 1867-1957; Cooking, American -- History -- Juvenile literature; Literary cookbooks; Cookery, American -- History; Literary cookbooks; Frontier and pioneer life